Efficacy and Safety of Rezūm System Water Vapor Treatment for Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia - Dixon, Christopher; Cedano, Edwin Rijo; Pacik, Dalibor; Vit, Viteslav; Varga, Gabriel; Wagrell, Lennart; Tornblom, Magnus; Mynderse, Lance; Larson, Thayne (Urology, 2015)
OBJECTIVE: To assess 1-year efficacy and safety data from pilot trials of the Rezūm System water vapor to treat lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). MATERIALS AND METHODS: A total of 65 men with symptoms of moderate to severe BPH were enrolled in pilot studies at centers in the Dominican Republic, the Czech Republic, and Sweden. Each patient was treated with transurethral delivery of sterile water vapor (steam). International Prostate Symptom Score (IPSS), peak urinary flow (Qmax), quality of life (QoL), postvoid residual, International Index of Erectile Function, and prostate-specific antigen were evaluated at 1 week and 1, 3, 6, and 12 months post-treatment. Safety was also assessed. RESULTS: Statistically significant clinical improvements at 1, 3, 6, and 12 months were reported for IPSS (decreased by 6.8, 13.4, 13.1, and 12.5 points, respectively) and Qmax (increased by 2.0, 4.7, 4.3, and 4.6 mL/sec, respectively). At 12 months, these results equated to a 56% improvement in IPSS (P <.001) and an 87% improvement in Qmax (P <.001). QoL also improved at 12 months with a 61% improvement. Sexual function was maintained. Most of the adverse events (AEs) were related to endoscopic instrumentation and were of short duration. One case of urinary retention was classified as a procedure/device-related serious AE. CONCLUSION: The Rezūm System provides effective relief of LUTS associated with BPH at 1 year. The procedure is safe with an acceptable side effect profile.
Keywords: symptomy dolních močových cest; Risk Assessment; následné studie; Prostatic Hyperplasia; lidé; Middle Aged; obnova funkce; výsledek terapie; Laser Therapy; hyperplazie prostaty; miniinvazivní chirurgické výkony; prospektivní studie; stupeň závažnosti nemoci; pilotní projekty; Internationality; interval spolehlivosti; hodnocení rizik; Pilot Projects; bezpečnost pacientů; internacionalita; Humans; Follow-Up Studies; Minimally Invasive Surgical Procedures; Prospective Studies; lidé středního věku; Patient Safety; Confidence Intervals; Urodynamics; mužské pohlaví; Severity of Illness Index; Lower Urinary Tract Symptoms; Transurethral Resection of Prostate; urodynamika; Male; Treatment Outcome; Aged; laserová terapie; transuretrální resekce prostaty; Recovery of Function; senioři